Menilai Faktor yang Mempengaruhi Penerapan edokumen dalam Pengurusan: Bahagian Sumber Manusia, Pejabat Setiausaha Kerajaan Negeri Kedah Darulaman - Putra, Irwansyah (2013)
Information technology has changed rapidly and has become the part of document management. Bahagian Sumber Manusia (BSM) Pejabat Setiausaha Kerajaan (SUK) Negeri Kedah has used eDokumen also known as Sistem Pengurusan Dokumen Jabatan since July 2011 to deal with document management. eDokumen developed and built by Pusat Teknologi Maklumat Negeri Kedah (PTMK) at 2007. eDokumen developed as an electronic media that can replace the function of paper and to provide proper management of documents. The main purpose of implementation eDokumen in BSM is to record original document by scanning process and to know the progress status of the document to ensure the document is settled in seven days of working day as the commitment of BSM. This study uses a Fishbone Diagram to identify the factors that influence the implementation of eDokumen in BSM with four factors; technical factors, policy factors, procedure factors and institutional factors. Technical factors have been well supported but this facility has not been used optimally. Policy and procedure factors are still using manual ways to valid the documents. Institutional factors also do not work well because eDokumen only used by some institutions actively in Pejabat SUK Negeri Kedah also institutions in Negeri Kedah Darulaman